Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa Materi Pengelompokan Hewan Berdasarkan Jenis Makanan Kelas V SDN 1 Lambheu Aceh Besar - Sri uning; Ahadin Ahadin; Suci Fitriani (Elementary Education Research, 2023)
The research was conducted to determine the relevant effect of using the Mind Mapping learning method on the acquisition of student learning outcomes on classifying animals based on the type of food Class V SDN 1 Lambheu Aceh Besar. This study uses a quantitative approach, the type is True Experimental (Pretest-Postest Control Group Design). This research was conducted in class V SDN 1 Lambheu Aceh Besar. Aceh Besar District, Darul Imarah District, on Jln Kreung Daroy Utama Perumnas Lambheu. Sampling was carried out using probability sampling/random sampling technique as a sample determination. The sample of this research is 50 students of class VA and VB. Data collection techniques used pretest and posttest, to analyze data using SPSS Statistics 24 and hypothesis testing with Paired Sample t-Test. The results of testing the hypothesis with the statistical paired sample t-test obtained a significance value (2-tailed) of 0.000 0.05. Then the decision is made, namely H_a is accepted and H_o is rejected. so that it can be concluded that there is a significant influence between the mind mapping learning model on student learning outcomes in animal grouping material, based on the type of food for class V SDN 1 Lambheu Aceh Besar.